PENGARUH PELATIHAN TERHADAP PENGETAHUAN DAN KETERAMPILAN KADER TENTANG DETEKSI DINI PENDENGARAN DAN PENGLIHATAN ANAK BALITA DI DESA AMBARKETAWANG WILAYAH PUSKESMAS GAMPING 1 SLEMAN YOGYAKARTA - , DIKI YUGE KATAN, Itsna Lutfi Kholisa, S.Kep., Ns., MANP ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In Indonesia, the childâs health promotion is a major concern because children are very vulnerable of developmental disorder . Meanwhile, mothers are still lack of knowledge about how to prevent the early development disorder of their children. A cadre in a CHCâs services need to education so they can continue the prevention through early detections. Objective: To understand the effect of a training on early detection in hearing and vision disorder of children on Cadres Knowledge and Skill in CHC Gamping I, Sleman Yogyakarta. Method: This research conducted using pre experimental design with One Group Pretest- Posttest of 30 participants from posyanduâs cadres. This study is using the knowledge questionnaires to measure the knowledge aspects, also using an observational checklists skill to measure the skills of early detection in hearing and visionâs developmental disorder of children. Results: Knowledge of posyanduâs cadres before training in hearing early detectionâs topic were mainly low (43,33%) and average level (43,33%) , after training their knowledge were mainly high (66,67%). Cadresâs knowledge before training in vision early detectionâs topic were mainly had average level (46,67%), after training their knowledge were mainly high (63,33%). As many as (42,31%) for average and (42,31%) for high level of skills on hearing early detection skills, and mainly (65,38%) had average level of vision early detectionâs skills. There was increment on knowledge of posyanduâs cadres before and after given a training with p<0,05. Conclusion: There is an increment of cadreâs knowledge after getting an early detectionâs training programme.